COVID‐19 as a frustrating event under Singapore contract law - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2020)
COVID-19 has had an unprecedented impact on commercial arrangements around the world. This would appear to fit the textbook definition of a frustrating event under Singapore contract law. Alternatively, one might expect COVID-19 to be covered by the doctrine of force majeure. This commentary will provide a brief overview of the contractual issues arising from COVID-19.